FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Hardityo Wibisono; Agus Purwanto (Diponegoro Journal of Accounting, 2015)
In this research, we provides the investigation over the acceptance of going concern audit opinion by observing the company’s internal condition such as the audit quality, company’s financial condition, audit opinion prior year, company growth, company size, debt to asset ratio, and opinion shopping. Samples are obtained by purposive samplingmethod and 138 observation data from 2008 - 2013 at manufacturing companies listed at Indonesia Stock Exchange. The logistic regression used to examine the factors that arepredicted to affect the probability of acceptance of going concern audit opinion. The result of this research indicate that debt to asset ratio affect the probability of acceptance ofgoing concern audit opinion and audit opinion prior year significantly affect the probability of acceptance of going concern audit opinion. On the other hand audit quality,company’s financial condition, company size, opinion shopping, company growth do not significantly acceptance of going concern audit opinion.